Profile of Caribbean services for international trade : [draft] - Blake, Byron ed. (CARICOM Secretariat GeorgetownGY, 1991)
Provides a preliminary statement on the case for identifying and developing certain service sectors in the Caribbean for international trade. Focuses attention on the range of issues which have fed the international debate on a multilateral framework agreement and on the needs and interests of the economies of developed and developing countries.